Análisis y diseño de la red de datos, para la implementación de la infraestructura tecnológica en la unidad de análisis financiero del Ecuador - Gaibor, Dalila Mirella (2014)
This paper aims to analyze and design the data network to implement the technology infrastructure in the Financial Analysis Unit of Ecuador, to which has been used concepts of convergence, mobility, scalability, interoperability, security, high availability. An analysis of the current state of the technological infrastructure of the institution, which allows us to propose a solution to the data network that meets the requirements of the IT services to be implemented in the institution, such as VoIP, video surveillance circuit IP cameras, email service, documentation system, and an estimate is made of the bandwidth that could be used for these services, as well as estimating the bandwidth to the Internet according to Institutional reality...